2023
DOI: 10.3390/plants13010046
|View full text |Cite
|
Sign up to set email alerts
|

Ion Changes and Signaling under Salt Stress in Wheat and Other Important Crops

Sylvia Lindberg,
Albert Premkumar

Abstract: High concentrations of sodium (Na+), chloride (Cl−), calcium (Ca2+), and sulphate (SO42−) are frequently found in saline soils. Crop plants cannot successfully develop and produce because salt stress impairs the uptake of Ca2+, potassium (K+), and water into plant cells. Different intracellular and extracellular ionic concentrations change with salinity, including those of Ca2+, K+, and protons. These cations serve as stress signaling molecules in addition to being essential for ionic homeostasis and nutrition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 319 publications
(461 reference statements)
0
3
0
Order By: Relevance
“…Barring S-, T- and S+T+F-stage, CSR36 exhibited significantly low Cl − accumulation in roots and transport low Cl − and high PO 4 3− to the shoots at critical growth stages (F-, S+T- and S+T+F+SS-stages) as compared with Jaya indicating ion selectivity and discrimination ( Figure S4A,B ) [ 40 ]. The low shoot Cl − concentration is maintained by restricting xylem-driven root to shoot transport (i) by higher Cl − efflux from the root to soil solution or (ii) by reducing the xylem loading as evident in CSR36 [ 50 ]. However, SO 4 2− and PO 4 3− are probably assimilated in plant metabolism [ 51 ] resulting enhanced plant growth and reduced internal concentration in roots and shoots as seen in the case of tolerant variety CSR36 under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Barring S-, T- and S+T+F-stage, CSR36 exhibited significantly low Cl − accumulation in roots and transport low Cl − and high PO 4 3− to the shoots at critical growth stages (F-, S+T- and S+T+F+SS-stages) as compared with Jaya indicating ion selectivity and discrimination ( Figure S4A,B ) [ 40 ]. The low shoot Cl − concentration is maintained by restricting xylem-driven root to shoot transport (i) by higher Cl − efflux from the root to soil solution or (ii) by reducing the xylem loading as evident in CSR36 [ 50 ]. However, SO 4 2− and PO 4 3− are probably assimilated in plant metabolism [ 51 ] resulting enhanced plant growth and reduced internal concentration in roots and shoots as seen in the case of tolerant variety CSR36 under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Barring S-, T-and S+T+F-stage, CSR36 exhibited significantly low Cl − accumulation in roots and transport low Cl − and high PO 4 3− to the shoots at critical growth stages (F-, S+Tand S+T+F+SS-stages) as compared with Jaya indicating ion selectivity and discrimination (Figure S4A,B) [40]. The low shoot Cl − concentration is maintained by restricting xylemdriven root to shoot transport (i) by higher Cl − efflux from the root to soil solution or (ii) by reducing the xylem loading as evident in CSR36 [50]. However, SO 4 2− and PO 4 3− are probably assimilated in plant metabolism [51] resulting enhanced plant growth and reduced internal concentration in roots and shoots as seen in the case of tolerant variety CSR36 under salt stress.…”
Section: Nacl-induced Disequilibrium In Micro-cations and Anionsmentioning
confidence: 96%
“…Further statistical analysis of these SNPs revealed that 167 were detected by both programs simultaneously, and they are relatively stable SNP loci (Table S5). These 167 SNPs were located on 21 of the 65 okra chromosomes, namely, chromosomes 4,5,15,17,19,22,24,25,31,37,40,41,43,44,45,46,54,56,59, 61, and 64. Among them, chromosome 31 had the most marker-trait associations (66) detected.…”
Section: Gwas Of Gp Under Ck and Salt Stress Conditionsmentioning
confidence: 99%
“…Soil salinization is an important environmental factor that affects germination, growth and development, and yield. Soil salinization poses a serious threat to global crop production [ 5 ].…”
Section: Introductionmentioning
confidence: 99%